2007
DOI: 10.1007/s11783-007-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of anaerobic phosphorus release during biological phosphorus removal process

Abstract: Enhanced biological phosphorus removal (EBPR) is a commonly used and sustainable method for phosphorus removal from wastewater. Poly-β-hydroxybutyrate (PHB), polyphosphate, and glycogen are three kinds of intracellular storage polymers in phosphorus accumulation organisms. The variation of these polymers under different conditions has an apparent influence on anaerobic phosphorus release, which is very important for controlling the performance of EBPR. To obtain the mechanism and kinetic character of anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Brdjanovic et al (1999) devised an assay, whereby the ratio of PAOs to GAOs could be estimated from acetate uptake during phosphorus release and after cessation of phosphorus release based on the assumption that acetate uptake by PAOs is limited by intracellular polyphosphate. However, this assumption was later refuted by others (Dou et al, 2007;Erdal et al, 2008;Zhou et al, 2008). Assuming that acetate uptake is independent of pH for PAOs, Filipe et al (2001c) suggested evaluating the presence of GAOs by comparing anaerobic acetate uptake in batch tests at pH 6.5 and 8.0.…”
Section: Competition Between Polyphosphate-and Glycogen-accumulating mentioning
confidence: 99%
See 1 more Smart Citation
“…Brdjanovic et al (1999) devised an assay, whereby the ratio of PAOs to GAOs could be estimated from acetate uptake during phosphorus release and after cessation of phosphorus release based on the assumption that acetate uptake by PAOs is limited by intracellular polyphosphate. However, this assumption was later refuted by others (Dou et al, 2007;Erdal et al, 2008;Zhou et al, 2008). Assuming that acetate uptake is independent of pH for PAOs, Filipe et al (2001c) suggested evaluating the presence of GAOs by comparing anaerobic acetate uptake in batch tests at pH 6.5 and 8.0.…”
Section: Competition Between Polyphosphate-and Glycogen-accumulating mentioning
confidence: 99%
“…The apparent weaknesses of using the P/HAc ratio as a surrogate for GAO dominance and its effect on plant performance also may be related to the fact that the ratio is dependent on a number of other factors. The P/HAc ratio has been reported to vary with initial substrate and sludge concentration (Romanski et al, 1997;Wentzel et al, 1985), pH (Filipe et al, 2001c;Smolders et al, 1994), organic carbon type (Jun and Shin, 1997), temperature , and intracellular glycogen and polyphosphate levels (Dou et al, 2007;Hesselmann et al, 2000;Liu et al, 1996a;Mino et al, 1987). In the literature, the P/ HAc ratio has been reported to vary from 0.2 to 0.9, for a successful phosphorus-removing system Schuler and Jenkins, 2003).…”
Section: Competition Between Polyphosphate-and Glycogen-accumulating mentioning
confidence: 99%
“…The supernatant was also harvested and mixed with the previous one, and then diluted to 50 mL. 2 mL solution was taken out and 2 drops of concentrated sulfuric acid were added and heated for 10 min at 100oC [5,6] . After the solution was cooled to room temperature, the phosphate concentration was determined with ammonium molybdate spectrophotometry [13] .…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The quantification determination of poly-P relies on chemical analysis which transforms the ntracellular poly-P into orthophosphate by perchloric and sulfuric acid and then determined with ammonium molybdate spectrophotometry [5,6] However, the procedure of these methods are tedious and may induce some operation errors, which cannot acquire the intracellular poly-P in time.…”
Section: Introductionmentioning
confidence: 99%
“…This test was divided into two parts: (i) Anaerobic phosphorus release pretreatment: Previous researchers found that the phosphorus contained in the biomass could be released as soluble phosphate under anaerobic conditions, whereas uptake could occur under aerobic conditions. Further, prior anaero- [24,25]. Consequently, the biofilm was pretreated under anaerobic condition since it might be phosphate saturated after a period of operation.…”
Section: Examination Of the Biofilms Phosphorus Storage Capacitymentioning
confidence: 99%